Analysis of the ASEAN Banking Integration Framework: The Philippines as a looking glass for consumer preference - Francis Lawrence B. De Jesus; Enrico Aurelio Torres (Journal of Global Entrepreneurship Research, 2017)
ASEAN, a region currently undergoing an ambitious integration initiative proposed a unified regional banking system thru the Qualified ASEAN Banks. This brings forth an array of competitive banking alternatives who are now capable of entering new economies within the ASEAN region. Would a local banking customer choose to adhere to the offers of these cross border alternatives or would they stick to their local homegrown banks? With banks from different members of the ASEAN Region as subjects and the local population of the Philippines as respondents, the study yielded the following results; Upon the full implementation of the ASEAN Banking Integration Framework up to 58.25% of the local market would diversify their savings resources between local banks and qualified ASEAN Banks, 77.50% would prioritize Qualified ASEAN Banks for their loans and financing requirements. This brings forth an important contemplation on how local and ASEAN banks should prepare for the full effects of this integration initiative.
Keywords: 650; ASEAN; Banking; Philippines; Integration